Does democracy flourish in the dark? Regional development and democracy building - Lucie Coufalová; Michaela Kecskésová; Stepan Mikula; Michal Ševčík (Masaryk University, Faculty of Economics and Administration, 2024)
This paper examines the impact of regional development on democracy building in the Czech Republic following the fall of the Iron Curtain and the autocratic communist regime in 1989. By exploiting the variation in regional development arising from the economic transition process, we identify that regional development, approximated by nighttime light intensity growth, leads to a rise in voter turnout in parliamentary elections. The heightened voter turnout is associated with increased electoral support for pro-system, pro-democratic parties, indicating that regional development facilitates democracy building. Conversely, we find no effect of regional development on the electoral support for the direct successor of the pre-1989 Communist Party. This suggests that while regional development may mitigate anti-system sentiment, it does not eliminate nostalgia for the fallen autocratic regime.
Keywords: D72; P25; O18; 330; economic voting; Czech parliamentary elections; democracy building; voter turnout; economic transition; nighttime lights; regional development; communotropic voting